Capturing Reality: The Art of Documentary - Ferrari, Pepita (Canada, 2008)
The world's best documentarians reflect upon the unique power of their genre in this comprehensive production. Featuring interviews with 38 directors and 163 film clips from classics such as "Grey Gardens" and "The Thin Blue Line", as well as recent work like "Darwin’s Nightmare" and "Touching the Void", "Capturing Reality" explores the complex creative process that goes into making non-fiction films. Deftly charting the documentarian’s journey, it poses the question: can film capture reality?